Mesothelioma – Cytological Studies and Medical Management in a Non-Descript Dog – A Case Report - Sundararajan, RC; K, Preethi; K, Gopal; D, Vishnugurubaran; V, Vijayanand; M, Balagangatharathilagar (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Mesotheliomas are tumors of low grade malignancy originating from mesothelial cells covering the coelomic cavities such as the pericardium, pleura, peritoneum and vaginal tunic (Seo et al., 2007). The three types of mesotheliomas are epithelial, fibrous (arcomatous) and biphasic (mixed). The epithelial form, which closely resembles the carcinoma and adenocarcinoma, is the most common type of mesothelioma in dogs (Echandi et al., 2007). Pleural effusion is one of the most classical characteristic feature of mesothelioma. They cause minimal tissue invasion and rarely metastasis to other regions (Vural et al., 2007). In addition to viral or genetic factors long term exposure to dusts such as asbestos, iron or silica plays a major role in the pathogenesis of this neoplasm. It is more common in older animals than younger animals (Echandi et al., 2007). The major clinical sign of this condition occurs due to the accumulation of fluid in the body cavities (Seo et al., 2007). The cytological analysis of the fluid helps to determine the cause of pleural effusion and to make rapid diagnosis (Martin et al., 2011). The morphology of the mesothelial cells are round to polygonal in outline, with anisocytosis, anisokaryosis, pleomorphic multi-nucleated cells, minimal eosinophilic or basophilic cytoplasm, mitosis, loose chromatin, evident nucleoli and ovoid to angulated vesicular nucleus (Martin et al., 2011).